Department of Registration and Stamps (Govt. of Mumbai) - Ghosh, Ayan (2023)
Other than the Asiatic Society, the Town Hall also houses the office of the Department of Registration and Stamps (Government of Mumbai) and the head office of the Directorate of Libraries (Maharashtra State), which runs the State Central Library, located inside the Town Hall.